2021
DOI: 10.3390/diagnostics11020377
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Usability of HCV Self-Testing in High Risk Populations in Vietnam

Abstract: HIV self-testing has emerged as a safe and effective approach to increase the access to and uptake of HIV testing and treatment, especially for key populations. Applying self-testing to hepatitis C virus (HCV) may also offer an additional way to address low coverage of HCV testing and to accelerate elimination efforts. To understand the potential for HCV self-testing (HCVST), an observational study was conducted to assess the acceptability and usability of the OraQuick® HCV Self-Test (prototype) among people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
30
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 17 publications
15
30
2
Order By: Relevance
“…Our ndings are consistent with a similar twin study carried out in Vietnam [32]. Researchers found that the number of MSM conducting HCVST correctly was signi cantly higher compared to PWID (66.3% vs 37.1%; p < 0.0001), owing to sociodemographic differences among PWID such as being older and less educated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our ndings are consistent with a similar twin study carried out in Vietnam [32]. Researchers found that the number of MSM conducting HCVST correctly was signi cantly higher compared to PWID (66.3% vs 37.1%; p < 0.0001), owing to sociodemographic differences among PWID such as being older and less educated.…”
Section: Discussionsupporting
confidence: 91%
“…Usability was assessed by calculating the frequencies of mistakes, di culties and assistance needed at each step of the testing procedure from opening the package to reading the results. Usability was de ned as the percentage of participants who completed the testing steps without assistance and interpreted results correctly [32]. The percent agreement along with the Cohen's Kappa coe cient was used to calculate inter-reader and interoperator agreement, both including all test results and excluding paired invalid test results.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies are going to be conducted in different countries to assess the usability and acceptability of HCV self-testing supported by FIND and using a testing platform donated by OraSure. Recently, an observational study was conducted in Vietnam to assess the acceptability and usability of the OraQuick ® HCV Self-Test (prototype) among PWIDs and MSM [ 90 ]. The study findings revealed overall high acceptability of HCVST with moderate to high usability among PWIDs (92.9%) and MSM (98.6%) in tested individuals.…”
Section: The Existing and Current Paradigms Of Hcv Diagnosticsmentioning
confidence: 99%
“…The study emphasizes enhancing support and assistance to optimize the acceptability and accelerated performance of HCVST in marginal populations (e.g., PWIDs, MSM, sex workers, homeless shelters, etc.) and for elderly people with low literacy or education levels [ 90 ].…”
Section: The Existing and Current Paradigms Of Hcv Diagnosticsmentioning
confidence: 99%